Cross-Cultural Comparisons of Coaching Styles and their Impact on Athlete Development in Greece and Chile - Haruto Nakamura, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
This research investigates the various coaching philosophies that are used in Chile and Greece and how they affect athletes' growth in the setting of their distinct cultures. The research offers insights into how coaching approaches in various nations differ and converge, influencing athlete results and adding to a deeper knowledge of sports culture. It does this by drawing upon historical, philosophical, and cultural elements. Greece's philosophical legacy is strongly ingrained in its coaching practices, which place a strong emphasis on tradition, collectivism, and all-inclusive development. Coaches place a high value on developing mentorship connections with their athletes and encouraging personal development in addition to physical achievement. The research based on quantitative analysis for determine the research used E-views software and generate results included descriptive statistic, correlation, unit root test analysis, also that present the equality test and histogram &state between them. Conversely, Chile's dynamic cultural backdrop and history of overcoming hardship are reflected in the country's coaching approaches, which are defined by adaptation, invention, and resilience. Coaches use customized strategies, incorporate a range of cultural influences, and place an emphasis on adaptability and ethnic pride. In spite of these distinctions, Greece and Chile both aim to develop athletes to the highest standards while substitute resiliency, personal development, and cultural identity. Coaches, athletes, and sports organizations may successfully exploit cultural assets in athlete development programs by tailoring these cross-cultural subtleties to their knowledge. Overall research founded that positive and significantly link between coaching style and their impact on athlete development. This study adds to the conversation on global sports culture and emphasizes how crucial it is for coaching and athlete development methods to take cultural context into account.